Bart’s syndrome associated with pyloric and choanal atresia - Narter, Fatma; Büyükbabani, Nesimi; Yararlı, Heybet; Öztürk, Şule; Ergüven, Müferet (The Turkish Journal of Pediatrics, 2013)
Bart’s syndrome, first described by Bart in 1966, consists of congenital localized absence of skin, congenital epidermolysis bullosa, and associated nail abnormalities. A newborn infant with Bart’s syndrome is reported since it is a very rare condition, especially when associated with pyloric and concomitant choanal atresia. To the best of our knowledge, this is the first report presenting a case of Bart’s syndrome associated with choanal atresia.